Pengukuran Beban Kerja Fisik Menggunakan Cardiovascular Load dan Evaluasi Postur Kerja untuk Mengurangi Keluhan Muskuloskeletal - Dharma Putra, Anak Agung Gede; Sekarjati*, Kartinasari Ayuhikmatin; Simanjuntak, Risma Adelina (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2023)
CV Dwi Jasa Logam is a company engaged in metal casting. This company places employees in jobs that are heavy on physical exertion in the production process, causing employees to get a high workload. In addition, many employees are elderly, causing them to feel tired more quickly. Employees who are placed on the job, need a longer rest time. When working, employees do not pay attention to work posture while working, so that poor work posture can cause musculoskeletal disorders. The purpose of this study was to analyze the physical workload of employees, analyze musculoskeletal disorders in employees and evaluate employees' poor work posture. The methods used are Cardiovascular Load (CVL), Nordic Body Map (NBM), Ovako Work Analysis System (OWAS). The CVL method is used to calculate physical workload, the NBM questionnaire is used to measure musculoskeletal disorders and identify musculoskeletal disorders and the OWAS method is a method used to assess body posture when working, which is related to body parts such as the back, arms, legs and heavy loads. Based on the results of data processing using the CVL method, there are 20 employees who have a moderate workload level and 10 employees who have a low workload level. Data processing using the NBM questionnaire shows that 8 employees have the highest score in the high risk category, while 22 employee’s other employees have moderate risk categories and data processing using the OWAS method for 8 employees gets category 2 and 3 results, namely improvements need to be made.